Coating slurry, composite current collector and preparation method thereof, and lithium ion battery
By using coating slurry prepared by using materials such as aqueous aliphatic polycarbon polyurethane and aqueous acrylic resin in the composite fluid collection, the coating is formed to improve the binding force between the conductive layer and the polymer substrate, the problem of insufficient performance of the composite fluid collection is solved, and the circulation performance and service life of the lithium-ion battery is significantly improved.
Patent Information
- Application Number
- CN202411862015.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
The mechanical strength of the polymer substrate in the existing composite fluids is insufficient, the band is easily broken, and the yield is low; the PI film is high in cost and cannot be used on a large scale; the PET film has poor solvent resistance, short circulation performance and life; the binding force between the conductive layer and the polymer substrate is low, which affects the energy density and service life of the lithium-ion battery.
Provided is a coating slurry, the main components are aqueous aliphatic polycarbon polyurethane dispersion, aqueous acrylic resin dispersion, curing agent and solvent. By coating on the surface of the polymer substrate, the bonding force between the conductive layer and the polymer substrate is improved, and the mechanical properties and electrochemical stability of the coating are enhanced.
The electrochemical stability, electrolyte resistance and binding force of the composite fluid collector are improved, the service life of the electrode is extended, the circulation performance and energy density of lithium-ion batteries are improved, and the problem of insufficient performance of the composite fluid collector in the prior art is solved.
Smart Images

Figure CN119662076A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of lithium-ion battery materials, and in particular to a coating slurry, a composite current collector and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] As an important component of lithium-ion batteries, current collectors play the role of collecting current and carrying negative electrode active materials. Their performance is directly related to the cycle life, energy density, safety performance, etc. of lithium-ion batteries. Traditional metal foil current collectors such as copper foil or aluminum foil have disadvantages such as large weight and high cost, which are difficult to meet people's increasingly high performance requirements for lithium-ion battery current collectors. In order to improve the performance of current collectors, composite current collectors have been developed in recent years. A metal layer with a thickness of about 1 micron is set on the upper and lower surfaces of polymer substrates such as polyethylene terephthalate film (PET film), biaxially oriented polypropylene film (BOPP film) or polyimide film (PI film). Compared with traditional metal foil current collectors, composite current collectors have the advantages of high conductivity, low cost and light weight.
[0003] However, in the existing composite current collector, the polymer substrate still has at least the following technical problems: the mechanical strength of the polymer substrate (such as BOPP film, etc.) is insufficient, and it is easy to break the belt as a carrier of the metal foil, and the yield is low; PI film, etc. cannot be used on a large scale due to its high cost; although some polymer substrates (such as PET film, etc.) have the characteristics of low cost, excellent mechanical properties, and good thermal stability, and can be well adapted to the processing technology of composite metal foil and electrode materials, such polymer substrates have poor solvent resistance, are prone to degradation and corrosion, and are easily reduced at low potentials. After being used as a composite current collector substrate to assemble a battery cell, the cycle performance is sharply attenuated and the cycle life is very short. In addition, the bonding force between the conductive layer and the polymer substrate in the existing composite current collector is generally low, which easily causes the risk of the conductive layer peeling off or falling off from the polymer substrate, thereby affecting the energy density and service life of the lithium-ion battery.
[0004] Therefore, how to propose a coating slurry, a composite current collector and a preparation method thereof, and a lithium-ion battery that can improve the performance of the composite current collector and the lithium-ion battery to solve or at least alleviate at least one of the above technical problems is a problem that needs to be solved urgently. Summary of the invention
[0005] In view of the above technical problems, the present disclosure provides a coating slurry, a composite current collector and a preparation method thereof, as well as a lithium-ion battery, to solve or at least alleviate at least one technical problem existing in the above polymer substrate and the technical problems caused by the composite current collector and the lithium-ion battery.
[0006] According to the specific embodiments of the present disclosure, in the first aspect, the present disclosure provides a coating slurry for a composite current collector, which is coated on the surface of a polymer substrate of the composite current collector. The main components of the coating slurry are: an aqueous aliphatic polycarbonate polyurethane dispersion, an aqueous acrylic resin dispersion, a curing agent and a solvent. The mass ratio of the aqueous aliphatic polycarbonate polyurethane dispersion, the aqueous acrylic resin dispersion, the curing agent and the solvent is: 5-10:15-25:0.2-1:64-79.8.
[0007] Optionally, the mass ratio of the aqueous aliphatic polycarbonate polyurethane dispersion, the aqueous acrylic resin dispersion, the curing agent and the solvent is: 6-8:18-20:0.48-0.56:71.44-75.52.
[0008] Optionally, the molecular weight of the aqueous aliphatic polycarbonate polyurethane in the aqueous aliphatic polycarbonate polyurethane dispersion is greater than 100,000.
[0009] Optionally, the waterborne aliphatic polycarbonate polyurethane has two glass transition temperatures, the first glass transition temperature is -20 to -30°C, and the second glass transition temperature is 90 to 100°C.
[0010] Optionally, the solid content of the aqueous aliphatic polycarbonate polyurethane dispersion is 25% to 35%, and the film-forming temperature is 0 to 20°C.
[0011] Optionally, the molecular weight of the aqueous acrylic resin in the aqueous acrylic resin dispersion is greater than 800,000.
[0012] Optionally, the glass transition temperature of the waterborne acrylic resin is 25-30°C.
[0013] Optionally, the solid content of the aqueous acrylic resin dispersion is 40% to 50%, and the film-forming temperature is 0 to 20°C.
[0014] Optionally, the curing agent includes at least one of aziridine, aziridine derivatives and polycarbodiimide.
[0015] Optionally, the solvent includes a mixture of one or more of water, ethanol, isopropanol, and butanone.
[0016] Optionally, the solvent includes water, or a mixture of water and one or more of ethanol, isopropanol, and butanone.
[0017] According to a specific embodiment of the present disclosure, in a second aspect, the present disclosure provides a method for preparing any coating slurry for a composite current collector as described above, characterized in that it comprises the following steps:
[0018] Step (T1), mixing the aqueous aliphatic polycarbonate polyurethane dispersion and the aqueous acrylic resin dispersion according to the mass ratio, stirring, to obtain a polymer mixture;
[0019] Step (T2), mixing the curing agent and the solvent according to the mass ratio, stirring, to obtain a curing agent dilution solution; and
[0020] Step (T3), adding the curing agent dilution to the polymer mixture under stirring, and after the addition is completed, increasing the stirring speed for dispersion to obtain the coating slurry.
[0021] Optionally, in step (T1), the stirring speed is 500 to 1000 rpm, and the stirring time is 20 to 35 min.
[0022] Optionally, in step (T2), the stirring speed is 300 to 600 rpm, and the stirring time is 10 to 15 min.
[0023] Optionally, in step (T3), the curing agent dilution is added to the polymer mixture at a stirring speed of 300 to 500 rpm, and after the addition is completed, the rotation speed is increased to 800 to 1500 rpm, and the mixture is dispersed for 15 to 20 minutes.
[0024] According to the specific embodiments of the present disclosure, in the third aspect, the present disclosure provides a composite current collector, including a polymer substrate, a coating and a conductive layer, wherein the coating is coated on the surface of the polymer substrate, and the conductive layer is arranged on the surface of the coating away from the polymer substrate, and the coating is coated on the surface of the polymer substrate using any coating slurry for the composite current collector as described above, and is formed after drying.
[0025] According to a specific embodiment of the present disclosure, in a fourth aspect, the present disclosure provides a method for preparing the composite current collector as described above, comprising the following steps:
[0026] Step (S1), performing surface corona treatment on the polymer substrate, with a corona power of 2.5 to 6 KW;
[0027] Step (S2), coating any of the aforementioned coating slurries for the composite current collector on at least one side of the polymer substrate obtained in step (S1), and drying to obtain a coated modified polymer substrate;
[0028] Step (S3), aging the coated modified polymer substrate in an environment of 45 to 60° C. for 24 to 60 hours to form the coating on at least one side of the polymer substrate; and
[0029] Step (S4), depositing the conductive layer on the side of the coating layer away from the polymer substrate to obtain the composite current collector.
[0030] According to the specific embodiments of the present disclosure, in the fifth aspect, the present disclosure provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet comprises the composite current collector and the positive electrode material as described above, and / or the negative electrode sheet comprises the composite current collector and the negative electrode material as described above.
[0031] Compared with the prior art, the above solution of the embodiment of the present disclosure has at least the following beneficial effects:
[0032] (1) The coating slurry disclosed in the present invention for composite current collectors includes both aqueous aliphatic polycarbon polyurethane dispersion and aqueous acrylic resin dispersion, which can form a coating with uniform distribution of soft phase and hard phase. The soft phase can release stress in the process of forming composite current collectors by physical vapor deposition (PVD) or chemical vapor deposition (CVD), reduce stress problems in composite current collector film formation, and improve product appearance; the hard phase can improve the mechanical strength of the coating. The coating slurry has good electrolyte resistance, and the formed coating can hinder the corrosion of the electrolyte to the polymer substrate, greatly improve the stability of the composite current collector in the electrolyte environment, and extend the service life of the electrode using the composite current collector; and the coating slurry has excellent electrochemical stability, and does not participate in electrochemical reactions at low voltages. Therefore, the coating formed by the coating slurry disclosed in the present invention does not participate in electrochemical reactions during battery operation, and can improve the service life of the electrode using the composite current collector. Therefore, the cycle performance and service life of lithium-ion batteries are greatly improved.
[0033] (2) The coating formed by the coating slurry disclosed herein does not contain or contains very little organic solvent, and the coating slurry is non-flammable, which is beneficial to the safety of the production environment and more in line with current environmental protection requirements. The coating slurry disclosed herein is applied to the surface of the polymer substrate to form a coating, which can effectively improve the bonding force between the polymer substrate and the conductive layer, prevent the conductive layer from falling off, and increase the energy density and service life of the lithium-ion battery. In addition, the production process of the coating slurry and the composite current collector disclosed herein is simple, low in cost, and high in efficiency, which is suitable for industrial production and is conducive to product promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The drawings herein are incorporated into the specification and constitute a part of the specification, showing embodiments consistent with the present disclosure, and together with the specification, are used to explain the principles of the present disclosure. Obviously, the drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:
[0035] Figure 1 A flow chart of a method for preparing a coating slurry for a composite current collector provided in an embodiment of the present disclosure;
[0036] Figure 2 A schematic diagram of the structure of a composite current collector provided in an embodiment of the present disclosure;
[0037] Figure 3 A flow chart of a method for preparing a composite current collector provided in an embodiment of the present disclosure.
[0038] The reference numerals in the specific implementation manner are as follows:
[0039] Composite current collector 100 , polymer substrate 10 , coating 20 , and conductive layer 30 . DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solutions and advantages of the present disclosure clearer, the present disclosure will be further described in detail below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present disclosure belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present disclosure.
[0042] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such product or device. In the absence of more restrictions, the elements defined by the sentence "comprises a" do not exclude the presence of other identical elements in the product or device including the elements.
[0043] In the description of the embodiments of the present disclosure, the orientation or positional relationship indicated by the technical terms "upper", "lower", "thickness", etc. is based on the orientation or positional relationship shown in the accompanying drawings, and is only for the convenience of describing the embodiments of the present disclosure and simplifying the description, rather than indicating or implying that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present disclosure.
[0044] In the description of the embodiments of the present disclosure, the term "and / or" is used only to describe the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0045] In the description of the embodiments of the present disclosure, the symbol “~” represents the two endpoint data before and after the “~” and all data between the two endpoints. For example, A~B represents all data greater than or equal to A and less than or equal to B.
[0046] Reference to "embodiments" in this disclosure means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the disclosure. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this disclosure may be combined with other embodiments.
[0047] The composite current collector is usually a sandwich structure, with the middle layer being a polymer substrate such as PET / BOPP / PI, and the upper and lower surfaces being metal conductive layers with a thickness of about 1 micron. Compared with traditional metal foil current collectors, composite current collectors have the advantages of high conductivity, low cost, and light weight.
[0048] However, the inventors have found through research that the polymer substrates in the existing composite current collectors still have at least the following technical problems: the mechanical strength of the polymer substrates (such as BOPP films, etc.) is insufficient, and it is easy to break the belt as a carrier of the metal foil, and the yield is low; PI films, etc. cannot be used on a large scale due to their high cost; although some polymer substrates (such as PET films, etc.) have the characteristics of low cost, excellent mechanical properties, and good thermal stability, and can be well adapted to the processing technology of composite metal foil and electrode materials, such polymer substrates have poor solvent resistance, are prone to degradation and corrosion, and are easily reduced at low potentials. After being used as composite current collector substrates to assemble battery cells, the cycle performance is sharply attenuated and the cycle life is very short. Moreover, the bonding force between the conductive layer and the polymer substrate in the existing composite current collector is generally low, which easily causes the risk of the conductive layer peeling off or falling off from the polymer substrate, thereby affecting the energy density and service life of the lithium-ion battery.
[0049] After research, the inventors also found that: although there are reports of coating solvent-based glue on the surface of the composite current collector to increase the bonding force between the polymer substrate and the conductive layer, the existing solvent-based glue uses a large amount of organic solvents, which has low safety, pollutes the environment and is costly; and the adhesive formed by the existing solvent-based glue after drying has poor solvent resistance, is easily corroded when immersed in the electrolyte, and has poor electrochemical stability. It is easy to participate in reactions during the use of the battery, affecting the energy density and service life of the lithium-ion battery.
[0050] In order to solve or at least alleviate the above technical problems, the present disclosure provides a coating slurry whose main components are aqueous aliphatic polycarbonate polyurethane dispersion, aqueous acrylic resin, curing agent and solvent by studying the coating slurry coated on the surface of the polymer substrate in the composite current collector. The coating formed by the coating slurry has good mechanical properties, electrochemical stability, adhesion, solvent resistance, safety and environmental protection, etc. It can improve the electrochemical stability, electrolyte resistance and bonding force of the composite current collector, thereby improving the cycle performance, safety performance and service life of the lithium-ion battery.
[0051] Specifically, an embodiment of the present disclosure provides a coating slurry for a composite current collector, which is coated on the surface of a polymer substrate of the composite current collector. The main components of the coating slurry are: an aqueous aliphatic polycarbonate polyurethane dispersion, an aqueous acrylic resin dispersion, a curing agent and a solvent. The mass ratio of the aqueous aliphatic polycarbonate polyurethane dispersion, the aqueous acrylic resin dispersion, the curing agent and the solvent is: 5 to 10: 15 to 25: 0.2 to 1: 64 to 79.8.
[0052] The present invention is used in the coating slurry of the composite current collector, which includes water-based aliphatic polycarbon polyurethane and water-based acrylic resin at the same time, and can form a coating with uniform distribution of soft phase and hard phase. The soft phase can release the stress in the process of forming the composite current collector by physical vapor deposition (PVD) or chemical vapor deposition (CVD), reduce the stress problem of the composite current collector film, and improve the product appearance; the hard phase can provide mechanical support, thereby improving the mechanical strength of the coating. The water-based aliphatic polycarbon polyurethane and the water-based acrylic resin have good electrolyte resistance, so that the coating slurry and the coating formed on the surface of the polymer substrate have good electrolyte resistance, which can hinder the corrosion of the electrolyte to the polymer substrate, greatly improve the stability of the composite current collector in the electrolyte environment, and extend the service life of the electrode using the composite current collector; and the coating slurry has excellent electrochemical stability, and does not participate in the electrochemical reaction within the range of 0 to 4.6V, so the coating in the composite current collector does not participate in the electrochemical reaction during the battery operation process, which is conducive to improving the service life of the electrode using the composite current collector. Therefore, the cycle performance and service life of the lithium-ion battery can be greatly improved. The coating slurry disclosed in the present invention does not contain or contains a very small amount of organic solvents. The coating slurry is non-flammable, which is beneficial to the safety of the production environment and is more in line with the current environmental protection requirements. It avoids the technical problems of the existing solvent-based glues that use a large amount of organic solvents, have low safety, pollute the environment, and so on. The present invention forms a coating by coating the coating slurry on the surface of the polymer substrate, which can effectively improve the bonding force between the polymer substrate and the conductive layer, effectively prevent the conductive layer from peeling off or falling off during the use of the battery, thereby increasing the energy density and service life of the lithium-ion battery, and solving the problem of the existing lithium-ion battery cycle capacity diving. In addition, the production process of the coating slurry and the composite current collector disclosed in the present invention is simple, low-cost, and high-efficiency, which is suitable for industrial production and is conducive to product promotion.
[0053] The optional embodiments of the present disclosure are described in detail below with reference to the accompanying drawings.
[0054] According to some embodiments of the present disclosure, the present disclosure provides a coating slurry for a composite current collector, the main components of which are: an aqueous aliphatic polycarbon polyurethane dispersion, an aqueous acrylic resin dispersion, a curing agent, and a solvent. It is understood that in some other embodiments, the coating slurry for the composite current collector may also be composed of an aqueous aliphatic polycarbon polyurethane dispersion, an aqueous acrylic resin dispersion, a curing agent, and a solvent.
[0055] In the coating slurry, the mass ratio of the aqueous aliphatic polycarbonate polyurethane dispersion, aqueous acrylic resin dispersion, curing agent and solvent is: 5-10:15-25:0.2-1:64-79.8. The mass ratio in this range can well balance the distribution of soft phase and hard phase in the coating, ensuring that the coating can release the stress generated during the evaporation process without significantly affecting the mechanical properties of the product; and the addition of an appropriate amount of curing agent can make the coating form a cross-linked and stable three-dimensional network structure, consume active groups, and further improve the coating's resistance to electrolyte corrosion. If the proportion of curing agent is too low, the degree of curing is insufficient, and the electrolyte immersion ability is insufficient. If the proportion of curing agent is too high, it will lead to small molecular by-products, and it will also reduce the open period of the coating liquid (the time from the preparation of the coating liquid to the change of physical properties to the unusable time), resulting in waste of coating liquid. In some preferred embodiments, the mass ratio of the aqueous aliphatic polycarbonate polyurethane dispersion, the aqueous acrylic resin dispersion, the curing agent and the solvent is: 6-8:18-20:0.48-0.56:71.44-75.52.
[0056] In some embodiments, the aqueous aliphatic polycarbonate polyurethane dispersion has two glass transition temperatures, the first glass transition temperature is -20 to -30°C, and the second glass transition temperature is 90 to 100°C; the glass transition temperature of the aqueous acrylic resin is 25 to 30°C. The coating slurry has three glass transition temperatures, and a coating with uniform distribution of soft phase and hard phase can be obtained. The soft phase can release the stress in the process of physical vapor deposition (PVD) and chemical vapor deposition (CVD) on the surface of the polymer substrate composite conductive layer, reduce the stress problem of the polymer substrate composite conductive layer film, and improve the product appearance; the hard phase can provide mechanical support, thereby improving the mechanical strength of the formed coating.
[0057] In some embodiments, the molecular weight of the aqueous aliphatic polycarbonate polyurethane in the aqueous aliphatic polycarbonate polyurethane dispersion is greater than 100,000, and / or the molecular weight of the aqueous acrylic resin in the aqueous acrylic resin dispersion is greater than 800,000, which is beneficial to improve the electrolyte resistance of the coating formed by the coating slurry, thereby preventing the corrosion of the polymer substrate by the electrolyte.
[0058] In some embodiments, the solid content of the aqueous aliphatic polycarbon polyurethane dispersion is 25% to 35%, and / or the solid content of the aqueous acrylic resin dispersion is 40% to 50%. The aqueous aliphatic polycarbon polyurethane dispersion and the aqueous acrylic resin dispersion within this solid content range have moderate viscosity, so that the subsequent materials are mixed evenly and the film is stable. In some embodiments, the film-forming temperature of the aqueous aliphatic polycarbon polyurethane dispersion is 0 to 20°C; and / or the film-forming temperature of the aqueous acrylic resin dispersion is 0 to 20°C.
[0059] In some embodiments, the curing agent includes, but is not limited to, at least one of aziridine, aziridine derivatives, and polycarbodiimide.
[0060] In some embodiments, the solvent includes but is not limited to a mixture of one or more of water, ethanol, isopropanol, and butanone. Preferably, the solvent includes water, or a mixture of water and at least one of ethanol, isopropanol, and butanone. In some embodiments, the solvent includes a mixed solvent formed by water and at least one of ethanol, isopropanol, and butanone, and the mass percentage of water in the mixed solvent is greater than or equal to 65%. The coating slurry disclosed herein does not contain or contains a small amount of organic solvent, and the coating slurry is non-flammable, which is beneficial to the safety of the production environment and is more in line with current environmental protection requirements.
[0061] See also Figure 1 According to some embodiments of the present disclosure, the present disclosure also provides a method for preparing any coating slurry for a composite current collector as described above, comprising the following steps:
[0062] Step (T1), mixing the aqueous aliphatic polycarbonate polyurethane dispersion and the aqueous acrylic resin dispersion according to a mass ratio, stirring, to obtain a polymer mixture;
[0063] Step (T2), mixing the curing agent and the solvent according to a mass ratio, stirring, and preparing a curing agent dilution solution; and
[0064] Step (T1), adding the curing agent dilution to the polymer mixture under stirring, and after the addition is completed, increasing the stirring speed for dispersion to obtain the coating slurry.
[0065] In some embodiments, in step (T1), the polymer mixture is stirred at a stirring speed of 500 to 1000 rpm for 20 to 35 minutes to obtain the polymer mixture. In some embodiments, in step (T2), the curing agent dilution is stirred at a stirring speed of 300 to 600 rpm for 10 to 15 minutes to obtain the curing agent dilution. In some embodiments, in step (T3), the curing agent dilution is added to the polymer mixture at a stirring speed of 300 to 500 rpm, and after the addition is completed, the stirring speed is increased to 800 to 1500 rpm, and dispersed for 15 to 20 minutes to obtain the coating slurry.
[0066] It can be understood that the order of step (T1) and step (T2) is only for the convenience of description and can be interchanged according to actual conditions.
[0067] See also Figure 2According to some embodiments of the present disclosure, the present disclosure further provides a composite current collector 100, comprising a polymer substrate 10, a coating 20 and a conductive layer 30, wherein the coating 20 is coated on the upper and lower surfaces of the polymer substrate 10, and the conductive layer 30 is disposed on the surface of the coating 20 away from the polymer substrate 10, and the coating 20 is coated on the upper and lower surfaces of the polymer substrate 10 using any of the aforementioned coating slurries for composite current collectors, and is formed after drying. It can be understood that in some other embodiments, the coating 20 may also be disposed only on the upper or lower surface of the polymer substrate 10.
[0068] In some embodiments, the polymer substrate 10 is a polyethylene terephthalate film (PET film). The PET film has the characteristics of low cost, excellent mechanical properties, and good thermal stability, and can be well adapted to the processing technology of electrode materials such as composite copper foil. After the PET film is coated with the coating 20, the embodiment of the present disclosure further improves the mechanical properties of the PET film and the adhesion between the conductive layer and the PET film, thereby preventing the conductive layer from peeling off or falling off the PET film; improves the electrochemical stability of the PET film, and does not participate in the electrochemical reaction within the low voltage range of 0 to 4.6V, which is beneficial to improve the service life of the lithium-ion battery electrode; improves the solvent resistance of the PET film, and is not easily degraded and corroded in the electrolyte. Therefore, the composite current collector of the embodiment of the present disclosure can improve the cycle capacity and service life of the lithium-ion battery, and effectively solves the problem of the cycle capacity diving after the existing PET composite current collector is used for electrode assembly batteries.
[0069] It is understandable that the polymer substrate 10 disclosed in the present invention is not limited to the PET film. In some other embodiments, it can also be a biaxially oriented polypropylene film (BOPP film), a polyimide film (PI film) or other commonly used polymer film materials for composite current collectors.
[0070] If the thickness of the coating 20 is too large, the volume and mass of the lithium-ion battery will increase, and the energy density of the lithium-ion battery will be reduced; if the thickness of the coating 20 is too small, the coating 20 cannot form a dense protective layer, and the protection ability of the polymer substrate 10 is insufficient; and the mechanical strength, solvent resistance, and electrochemical stability of the polymer substrate 10 are insufficiently improved. In some embodiments, the thickness of the coating 20 is preferably, but not limited to, 0.2 to 3 μm.
[0071] In some embodiments, the composite current collector 100 is a positive electrode current collector, and the conductive layer 30 may be a common conductive layer of a positive electrode current collector, and may be, but not limited to, a metal aluminum layer or a composite aluminum layer, etc. In some other embodiments, the composite current collector 100 is a negative electrode current collector, and the conductive layer 30 may be a common conductive layer of a negative electrode current collector, and may be, but not limited to, a metal copper layer, a composite copper layer, etc. In this embodiment, the composite current collector 100 is a negative electrode current collector, and the conductive layer 30 is a metal copper layer.
[0072] See also Figure 3 According to some embodiments of the present disclosure, the present disclosure also provides a method for preparing the composite current collector 100 as described above, comprising the following steps:
[0073] Step (S1), performing surface corona treatment on the polymer substrate 10, with a corona power of 2.5 to 6 KW;
[0074] Step (S2), coating any of the aforementioned coating slurries for the composite current collector on at least one side of the polymer substrate obtained in step (S1), and drying to obtain a coated modified polymer substrate;
[0075] Step (S3), aging the coated modified polymer substrate in an environment of 45 to 60° C. for 24 to 60 hours to form the coating 20 on at least one side of the polymer substrate; and
[0076] Step ( S4 ), depositing the conductive layer 30 on the side of the coating layer 20 away from the polymer substrate 10 to obtain the composite current collector 100 .
[0077] In step (S1), the surface of the polymer substrate 10 is subjected to corona treatment, which can improve the surface adhesion of the polymer substrate 10 and facilitate the adhesion of the coating slurry.
[0078] In step (S2), the coating method may include but is not limited to gravure coating, micro-concave coating, dip coating, etc. In some embodiments, the coating speed is 80-150 mpm.
[0079] In step (S3), the coated modified polymer substrate is aged in an environment of 45-60°C for 24-60 hours to ensure that the coating is completely cured. The thickness of the coating 20 formed after curing is preferably but not limited to 0.2-3 μm.
[0080] In step (S4), the conductive layer 30 may be deposited on the surface of the coating 20 by at least one of physical vapor deposition (PVD), chemical vapor deposition (CVD), glue compounding, etc., but not limited to the above.
[0081] According to some embodiments of the present disclosure, the present disclosure further provides an electrode sheet, comprising the composite current collector 100 as described above and an electrode material disposed on the surface of the composite current collector 100. The electrode sheet may be a positive electrode sheet or a negative electrode sheet.
[0082] It can be understood that when the electrode sheet is a positive electrode sheet, the conductive layer 30 of the composite current collector 100 in the positive electrode sheet can be a common conductive layer of a positive electrode collector, including but not limited to a metal aluminum layer or a composite aluminum layer, etc.; the electrode material can be a common positive electrode material in a lithium-ion battery. When the electrode sheet is a negative electrode sheet, the conductive layer 30 of the composite current collector 100 in the negative electrode sheet can be a common conductive layer of a negative electrode collector, including but not limited to a metal copper layer, a composite copper layer, etc.; the electrode material can be a common negative electrode material in a lithium-ion battery.
[0083] According to some embodiments of the present disclosure, the present disclosure further provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet and / or the negative electrode sheet adopt the electrode sheet as described above. That is, the positive electrode sheet comprises the composite current collector 100 and a positive electrode material, and / or the negative electrode sheet comprises the composite current collector 100 and a negative electrode material.
[0084] The conductive layer 30 of the composite current collector 100 in the positive electrode sheet may be a common conductive layer of a positive electrode current collector, including but not limited to a metal aluminum layer or a composite aluminum layer, etc. The conductive layer 30 of the composite current collector 100 in the negative electrode sheet may be a common conductive layer of a negative electrode current collector, including but not limited to a metal copper layer, a composite copper layer, etc. In this embodiment, the negative electrode sheet includes the composite current collector 100 and a negative electrode material, and the conductive layer 30 in the composite current collector 100 is a copper foil.
[0085] The preparation process, test methods and test data of the embodiments and comparative examples are introduced below:
[0086] Embodiment 1:
[0087] The coating slurry is prepared, comprising the following steps:
[0088] Step (T1), mixing 6 parts of water-based aliphatic polycarbonate polyurethane and 20 parts of water-based acrylic polymer by weight, stirring at a stirring speed of 800 rpm for 30 minutes to obtain a polymer mixture;
[0089] Step (T2), mixing 0.52 parts of aziridine and a solvent, wherein the solvent consists of 50 parts of water and 23.48 parts of isopropanol, and stirring at a stirring speed of 500 rpm for 15 minutes to obtain the curing agent dilution; and
[0090] Step (T3), adding the curing agent dilution to the polymer mixture at a stirring speed of 400 rpm, increasing the rotation speed to 1200 rpm after the addition is completed, and dispersing for 20 minutes to obtain a coating slurry for standby use.
[0091] The preparation of the composite current collector comprises the following steps:
[0092] Step (S1), performing surface corona treatment on the PET film, with a corona power of 5KW;
[0093] Step (S2), coating the coating slurry prepared above on both sides of the PET film prepared in step (S1), and drying to obtain a coated modified PET film, the coating speed being 120 mpm;
[0094] Step (S3), curing the PET film obtained in step (S2) in an environment of 55° C. for 50 hours, and forming a 0.25 μm coating on both sides of the PET film; and
[0095] Step (S4), depositing a copper layer on both sides of the PET film obtained in step (S3) to obtain a composite current collector.
[0096] Embodiment 2:
[0097] The coating slurry is prepared, comprising the following steps:
[0098] Step (T1), mixing 8 parts of water-based aliphatic polycarbonate polyurethane and 15 parts of water-based acrylic polymer by weight, stirring at a stirring speed of 800 rpm for 30 minutes to obtain a polymer mixture;
[0099] Step (T2), mixing 0.46 parts of aziridine and a solvent, wherein the solvent consists of 50 parts of water and 26.54 parts of ethanol, and stirring at a stirring speed of 500 rpm for 15 minutes to obtain the curing agent dilution; and
[0100] Step (T3), adding the curing agent dilution to the polymer mixture at a stirring speed of 400 rpm, increasing the rotation speed to 1200 rpm after the addition is completed, and dispersing for 20 minutes to obtain a coating slurry for standby use.
[0101] The preparation of the composite current collector comprises the following steps:
[0102] Step (S1), performing surface corona treatment on the PET film, with a corona power of 5KW;
[0103] Step (S2), coating the coating slurry prepared above on both sides of the PET film prepared in step (S1), and drying to obtain a coated modified PET film, the coating speed being 120 mpm;
[0104] Step (S3), curing the PET film obtained in step (S2) in an environment of 55° C. for 50 hours, forming a 1.1 μm coating on both sides of the PET film; and
[0105] Step (S4), depositing a copper layer on both sides of the PET film obtained in step (S3) to obtain a composite current collector.
[0106] Embodiment 3:
[0107] The coating slurry is prepared, comprising the following steps:
[0108] Step (T1), mixing 5 parts of polyurethane resin and 25 parts of waterborne acrylic resin by weight, stirring at a stirring speed of 800 rpm for 30 minutes to obtain a polymer mixture;
[0109] Step (T2), mixing 0.75 parts of carbodiimide and a solvent, wherein the solvent consists of 45 parts of water and 14.25 parts of isopropanol, and stirring at a stirring speed of 500 rpm for 15 minutes to obtain the curing agent dilution; and
[0110] Step (T3), adding the curing agent dilution to the polymer mixture at a stirring speed of 400 rpm, increasing the rotation speed to 1200 rpm after the addition is completed, and dispersing for 20 minutes to obtain a coating slurry for standby use.
[0111] The preparation of the composite current collector comprises the following steps:
[0112] Step (S1), performing surface corona treatment on the PET film, with a corona power of 5KW;
[0113] Step (S2), coating the coating slurry prepared above on both sides of the PET film prepared in step (S1), and drying to obtain a coated modified PET film, the coating speed being 120 mpm;
[0114] Step (S3), curing the PET film obtained in step (S2) in an environment of 55° C. for 50 hours, and forming a 2.9 μm coating on both sides of the PET film; and
[0115] Step (S4), depositing a copper layer on both sides of the PET film obtained in step (S3) to obtain a composite current collector.
[0116] Embodiment 4:
[0117] The coating slurry is prepared, comprising the following steps:
[0118] Step (T1), mixing 7.5 parts of water-based aliphatic polycarbonate polyurethane and 19 parts of water-based acrylic polymer by weight, stirring at a stirring speed of 800 rpm for 30 minutes to obtain a polymer mixture;
[0119] Step (T2), mixing 0.53 parts of aziridine and a solvent, wherein the solvent consists of 54.97 parts of water and 18 parts of isopropanol, and stirring at a stirring speed of 500 rpm for 15 minutes to obtain the curing agent dilution; and
[0120] Step (T3), adding the curing agent dilution to the polymer mixture at a stirring speed of 400 rpm, increasing the rotation speed to 1200 rpm after the addition is completed, and dispersing for 20 minutes to obtain a coating slurry for standby use.
[0121] The preparation of the composite current collector comprises the following steps:
[0122] Step (S1), performing surface corona treatment on the PET film, with a corona power of 5KW;
[0123] Step (S2), coating the coating slurry prepared above on both sides of the PET film prepared in step (S1), and drying to obtain a coated modified PET film, the coating speed being 120 mpm;
[0124] Step (S3), curing the PET film obtained in step (S2) in an environment of 55° C. for 50 hours, and forming a 1.3 μm coating on both sides of the PET film; and
[0125] Step (S4), depositing a copper layer on both sides of the PET film obtained in step (S3) to obtain a composite current collector.
[0126] Embodiment 5:
[0127] The coating slurry is prepared, comprising the following steps:
[0128] Step (T1), mixing 9 parts of water-based aliphatic polycarbonate polyurethane and 15 parts of water-based acrylic polymer by weight, stirring at a stirring speed of 800 rpm for 30 minutes to obtain a polymer mixture;
[0129] Step (T2), mixing 0.5 parts of aziridine with a solvent, wherein the solvent consists of 50 parts of water and 25.5 parts of isopropanol, and stirring at a stirring speed of 500 rpm for 15 minutes to obtain the curing agent dilution; and
[0130] Step (T3), adding the curing agent dilution to the polymer mixture at a stirring speed of 400 rpm, increasing the rotation speed to 1200 rpm after the addition is completed, and dispersing for 20 minutes to obtain a coating slurry for standby use.
[0131] The preparation of the composite current collector comprises the following steps:
[0132] Step (S1), performing surface corona treatment on the PET film, with a corona power of 5KW;
[0133] Step (S2), coating the coating slurry prepared above on both sides of the PET film prepared in step (S1), and drying to obtain a coated modified PET film, the coating speed being 120 mpm;
[0134] Step (S3), curing the PET film obtained in step (S2) in an environment of 55° C. for 50 hours, and forming a 0.9 μm coating on both sides of the PET film; and
[0135] Step (S4), depositing a copper layer on both sides of the PET film obtained in step (S3) to obtain a composite current collector.
[0136] Embodiment 6:
[0137] The coating slurry is prepared, comprising the following steps:
[0138] Step (T1), mixing 10 parts of polyurethane resin and 17 parts of waterborne acrylic resin by weight, stirring at a stirring speed of 800 rpm for 30 minutes to obtain a polymer mixture;
[0139] Step (T2), mixing 0.4 parts of carbodiimide with a solvent, wherein the solvent consists of 60 parts of water and 12.6 parts of ethanol, and stirring at a stirring speed of 500 rpm for 15 minutes to obtain the curing agent dilution; and
[0140] Step (T3), adding the curing agent dilution to the polymer mixture at a stirring speed of 400 rpm, increasing the rotation speed to 1200 rpm after the addition is completed, and dispersing for 20 minutes to obtain a coating slurry for standby use.
[0141] The preparation of the composite current collector comprises the following steps:
[0142] Step (S1), performing surface corona treatment on the PET film, with a corona power of 56KW;
[0143] Step (S2), coating the coating slurry prepared above on both sides of the PET film prepared in step (S1), and drying to obtain a coated modified PET film, the coating speed being 120 mpm;
[0144] Step (S3), curing the PET film obtained in step (S2) in an environment of 55° C. for 50 hours, and forming a 1.7 μm coating on both sides of the PET film; and
[0145] Step (S4), depositing a copper layer on both sides of the PET film obtained in step (S3) to obtain a composite current collector.
[0146] Comparative Example 1:
[0147] The polymer substrate is a PET film material without coating, and the composite current collector is obtained by directly depositing a copper layer on the PET film material.
[0148] Comparative Example 2:
[0149] The coating slurry is prepared, comprising the following steps:
[0150] Step (T1), mixing 3 parts of polyurethane resin and 27 parts of waterborne acrylic resin by weight, stirring at a stirring speed of 800 rpm for 30 minutes to obtain a polymer mixture;
[0151] Step (T2), adding a solvent consisting of 60 parts of water and 10 parts of ethanol to the polymer mixture at a stirring speed of 500 rpm, increasing the speed to 1200 rpm after the addition, and dispersing for 20 minutes to obtain a coating slurry for standby use.
[0152] The preparation of the composite current collector comprises the following steps:
[0153] Step (S1), performing surface corona treatment on the PET film, with a corona power of 5KW;
[0154] Step (S2), coating the coating slurry prepared above on both sides of the PET film prepared in step (S1), and drying to obtain a coated modified PET film, the coating speed being 120 mpm;
[0155] Step (S3), curing the PET film obtained in step (S2) in an environment of 55° C. for 50 hours, forming a 0.8 μm coating on both sides of the PET film; and
[0156] Step (S4), depositing a copper layer on both sides of the PET film obtained in step (S3) to obtain a composite current collector.
[0157] The composite current collectors obtained in Examples 1-6 and Comparative Examples 1-2 were used as negative current collectors to assemble button-type half-cells. Except for the different negative current collectors, the other components were the same. The positive electrode of the battery used lithium iron phosphate, the negative electrode used graphite, and the electrolyte used Hairong 9212 electrolyte.
[0158] The adhesion of the copper layer on the PET film in the composite current collector obtained in Examples 1-6 and Comparative Example 1-2, the adhesion of the copper layer on the PET film after the composite current collector was immersed in 85°C Hairong 9212 electrolyte for 3 days, and the number of cycle cycles of the button half-battery assembled with the composite current collectors in Examples 1-6 and Comparative Example 1-2 when the charge and discharge rate was 1C and the battery capacity decayed to 80% were tested, and the test results are shown in Table 1.
[0159] The test method of bonding strength is as follows: fix one side of the composite current collector on the stainless steel plate with double-sided tape, hot-press the EAA glue on the other side of the composite current collector, and use a tensile testing machine to extend 180° and pull it apart. The test result is the adhesion of the copper layer.
[0160] Table 1 Test data of Examples 1-6 and Comparative Example 1
[0161]
[0162] From the comparison of the results of Examples 1-6 and Comparative Examples 1-2 in Table 1, it can be seen that the adhesion of the copper layer of the composite current collectors of Examples 1-6 before and after immersion in the electrolyte is much greater than that of Comparative Examples 1-2, and after immersion in the electrolyte, the adhesion of the copper layer of the composite current collectors of Examples 1-6 is only slightly attenuated, while the copper layer of the composite current collector in Comparative Example 1 delaminated after immersion in the electrolyte, and the adhesion of the copper layer of the composite current collector in Comparative Example 2 was also significantly attenuated after immersion in the electrolyte. It is explained that the coating formed by the coating slurry of the embodiment of the present invention can greatly improve the bonding force between the copper layer and the PET film material in the composite current collector; and the aqueous aliphatic polycarbonate polyurethane and aqueous acrylic resin in the coating slurry have good electrolyte resistance, therefore, the stability of the composite current collector in the electrolyte can be improved, and the addition of an appropriate amount of curing agent can make the coating form a cross-linked and stable three-dimensional network structure, consume active groups, and further improve the coating's resistance to electrolyte corrosion, ensuring that the composite current collector is immersed in the electrolyte for a long time, and there is still good bonding between the copper layer and the PET film material, and the copper layer does not peel off or fall off, thereby improving the service life of the composite current collector.
[0163] The comparison of the results of Examples 1-6 and Comparative Examples 1-2 in Table 1 also shows that under the same charge and discharge rate, when the battery capacity decays to 80%, the number of cycle cycles of the button half-cell assembled by the composite current collectors of Examples 1-6 is much greater than that of Comparative Examples 1-2. It is shown that the composite current collector with a coating in the embodiment of the present disclosure can greatly improve the cycle performance of the lithium-ion battery. This is because the coating of the embodiment of the present disclosure can not only increase the bonding force between the copper layer and the PET film material and increase the electrolyte resistance, but also the coating slurry of the embodiment of the present disclosure has excellent electrochemical stability. In the range of 0 to 4.6V, it does not participate in the electrochemical reaction. Therefore, the coating in the composite current collector does not participate in the electrochemical reaction during the operation of the battery, which is beneficial to improve the cycle performance of the lithium-ion battery; and the coating of the embodiment of the present disclosure is continuous and seamless, which can effectively prevent the acidic substances produced by the lithium-ion battery reaction from penetrating into the PET film material, alleviate the corrosion of the electrolyte to the PET film material, and avoid or at least alleviate the problems of shedding and aging that may occur in the existing composite current collector during long-term use, thereby improving the cycle performance and service life of the lithium-ion battery.
[0164] Moreover, the comparison of the results of Examples 1-6 and Comparative Example 2 also shows that the coating slurry provided by the embodiments of the present disclosure, wherein the mass fraction ratio of the aqueous aliphatic polycarbon polyurethane dispersion, aqueous acrylic resin dispersion, curing agent and solvent is 5-10:15-25:0.2-1:64-79.8, has significantly better adhesion, stability and other properties than the coating slurry without adding curing agent and the mass fraction ratio of other components outside the scope of the present disclosure. It further shows that the components and their mass fraction ratio ranges in the coating slurry of the embodiments of the present disclosure can greatly improve the adhesion and stability of the coating slurry, thereby improving the mechanical properties, electrochemical stability, solvent resistance, and bonding strength between the conductive layer and the polymer substrate of the composite current collector.
[0165] In summary, it can be concluded that the embodiment of the present disclosure can greatly improve the mechanical properties, electrochemical stability, solvent resistance, and bonding between the conductive layer and the polymer substrate of the composite current collector by coating the coating slurry whose main components are aqueous aliphatic polycarbon polyurethane dispersion, aqueous acrylic resin dispersion, curing agent and solvent on the surface of the PET film, and controlling the mass fraction ratio of each component within a certain range, thereby improving the cycle performance and service life of the lithium-ion battery, and meeting the demand for high-performance batteries in the field of battery manufacturing. The coating slurry of the embodiment of the present disclosure is simple and efficient to prepare, with low energy consumption, which is in line with the current trend of green development and meets the new demand for environmental protection and energy saving in the field of composite material science. The coating preparation equipment in the composite current collector of the embodiment of the present disclosure has small investment and low cost, which is conducive to large-scale production and application, and meets the demand for efficient and low-cost production methods in the field of coating preparation technology. Therefore, the coating slurry, composite current collector and preparation method thereof provided by the present disclosure, as well as lithium-ion batteries have broad market prospects and application potential in the application fields of battery manufacturing, composite material science and coating preparation.
[0166] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present disclosure, rather than to limit them; although the present disclosure has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present disclosure, and they should all be included in the scope of the claims and specification of the present disclosure. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present disclosure is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A coating slurry for a composite current collector, the coating slurry being coated on the surface of a polymer substrate of the composite current collector, characterized in that: The main components of the coating slurry are: aqueous aliphatic polycarbonate polyurethane dispersion, aqueous acrylic resin dispersion, curing agent and solvent, and the mass ratio of the aqueous aliphatic polycarbonate polyurethane dispersion, aqueous acrylic resin dispersion, curing agent and solvent is: 5-10:15-25:0.2-1:64-79.
8.
2. The coating slurry for a composite current collector according to claim 1, characterized in that: The mass ratio of the aqueous aliphatic polycarbonate polyurethane dispersion, the aqueous acrylic resin dispersion, the curing agent and the solvent is: 6-8:18-20:0.48-0.56:71.44-75.
52.
3. The coating slurry for a composite current collector according to claim 1, characterized in that: The molecular weight of the aqueous aliphatic polycarbonate polyurethane in the aqueous aliphatic polycarbonate polyurethane dispersion is greater than 100,000; And / or, the waterborne aliphatic polycarbonate polyurethane has two glass transition temperatures, the first glass transition temperature is -20 to -30°C, and the second glass transition temperature is 90 to 100°C; And / or, the solid content of the aqueous aliphatic polycarbonate polyurethane dispersion is 25% to 35%, and the film-forming temperature is 0 to 20°C.
4. The coating slurry for a composite current collector according to claim 1, characterized in that: The molecular weight of the aqueous acrylic resin in the aqueous acrylic resin dispersion is greater than 800,000; And / or, the glass transition temperature of the waterborne acrylic resin is 25 to 30°C; And / or, the solid content of the aqueous acrylic resin dispersion is 40% to 50%, and the film-forming temperature is 0 to 20°C.
5. The coating slurry for a composite current collector according to any one of claims 1 to 4, characterized in that: The curing agent includes at least one of aziridine, aziridine derivatives and polycarbodiimide; And / or, the solvent includes a mixture of one or more of water, ethanol, isopropanol, and butanone.
6. A method for preparing a coating slurry for a composite current collector according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step (T1), mixing the aqueous aliphatic polycarbonate polyurethane dispersion and the aqueous acrylic resin dispersion according to the mass ratio, stirring, to obtain a polymer mixture; Step (T2), mixing the curing agent and the solvent according to the mass ratio, stirring, and preparing a curing agent dilution solution; as well as Step (T3), adding the curing agent dilution to the polymer mixture under stirring, and after the addition is completed, increasing the stirring speed for dispersion to obtain the coating slurry.
7. The method for preparing a coating slurry for a composite current collector according to claim 6, characterized in that: In step (T1), the stirring speed is 500 to 1000 rpm, and the stirring time is 20 to 35 min; And / or, in step (T2), the stirring speed is 300 to 600 rpm and the stirring time is 10 to 15 min; And / or, in step (T3), the curing agent dilution is added to the polymer mixture at a stirring speed of 300 to 500 rpm, and after the addition is completed, the rotation speed is increased to 800 to 1500 rpm, and the mixture is dispersed for 15 to 20 minutes.
8. A composite current collector, characterized in that: The invention comprises a polymer substrate, a coating and a conductive layer, wherein the coating is coated on the surface of the polymer substrate, the conductive layer is arranged on the surface of the coating away from the polymer substrate, and the coating is coated on the surface of the polymer substrate using the coating slurry for the composite current collector as described in any one of claims 1 to 5, and is formed after drying.
9. A method for preparing a composite current collector as claimed in claim 8, characterized in that: The steps include: Step (S1), performing surface corona treatment on the polymer substrate, with a corona power of 2.5 to 6 KW; Step (S2), coating the coating slurry for the composite current collector according to any one of claims 1 to 5 on at least one side of the polymer substrate obtained in step (S1), and drying to obtain a coated modified polymer substrate; Step (S3), aging the coated modified polymer substrate in an environment of 45 to 60° C. for 24 to 60 hours to form the coating on at least one side of the polymer substrate; as well as Step (S4), depositing the conductive layer on the side of the coating layer away from the polymer substrate to obtain the composite current collector.
10. A lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, characterized in that: The positive electrode sheet comprises the composite current collector and the positive electrode material as claimed in claim 8, and / or the negative electrode sheet comprises the composite current collector and the negative electrode material as claimed in claim 8.
Citation Information
Cited By
Composite current collector and preparation method thereof, battery electrode and sodium ion battery
CN120834212A